The Economic Benefit Of Internship Program For Economics and Business Students - Kencana, Fawwaz Ardhan; Wiranatakusuma, Dimas Bagus; Aprizal , Anggi (Jurnal Manajemen, Akuntansi, Ekonomi, 2025)
The purpose of this research is to identify the financial benefits offered by internship programs for students of the Faculty of Economics and Business, particularly in relation to the increase in income during their studies and its impact on salary expectations after graduation. This study was conducted using a qualitative approach and case study. Data were collected through in-depth interviews with three students who participated in internship programs at financial institutions, namely the Financial Services Authority (OJK) and Bank Syariah Indonesia (BSI). The research results show that each respondent experienced an increase in income during the internship, which helped them finance their education. Additionally, two out of three respondents stated that the internship experience increased their salary expectations after graduation. These findings indicate that educational institutions should help students gain relevant work experience. So, internship programs not only enhance students' skills and prepare them for work, but also provide real financial benefits during their studies and help them choose their career paths in the future.